Hebbian and Homeostatic Synaptic Plasticity—Do Alterations of One Reflect Enhancement of the Other? - Galanis, Christos; Vlachos, Andreas (Frontiers in Cellular Neuroscience, 2020)
During the past 50 years, the cellular and molecular mechanisms of synaptic plasticity have been studied in great detail. A plethora of signalling pathways have been identified that account for synaptic changes based on positive and negative feedback mechanisms. Yet, the biological significance of Hebbian synaptic plasticity (= positive feedback) and homeostatic synaptic plasticity (= negative feedback) remains a matter of debate. Specifically, it is unclear how these opposing forms of plasticity, which share common downstream mechanisms, operate in the same networks, neurons, and synapses. Based on the observation that rapid and input-specific homeostatic mechanisms exist, we here discuss a model which is based on signalling pathways that may adjust a balance between Hebbian and homeostatic synaptic plasticity. Hence, ‘alterations’ in Hebbian plasticity may, in fact, resemble ‘enhanced’ homeostasis, which rapidly returns synaptic strength back to baseline. In turn, long-lasting experience-dependent synaptic changes may require an attenuation of homeostatic mechanisms or the adjustment of homeostatic setpoints at the single-synapse level. In this context, we propose a role for the proteolytic processing of the amyloid precursor protein (APP) in setting a balance between the ability of neurons to express Hebbian and homeostatic synaptic plasticity.